IN MEMORIAM PROFESSOR ANWARI DILMY - a. j. g. h. kostermans (Reinwardtia, 1982)
With the death of Professor Anwari Dilmy on 25 April 1979, Indonesia lost a man who contributed a large part of his life to safeguard the valuable collections of the Herbarium Bogoriense of the National Biological Institute.